From super-yachts to web isolation. Issue 12 (December 2017) - Kelley, Jay
Abstract : Even the super-luxurious boats owned by the jet-setting rich and famous are being taken hostage. 1 A white-hat hacker at a recent super-yacht investor conference (who knew there even were such events?) demonstrated, in less than 30 minutes, how he took control of a super-yacht's satellite communications system, meaning that the cyber-pirates had control over the ship's wifi, telephone system and even the navigation system. 2 He could read emails, gather banking information and even steer the boat totally off-course without the ship's crew being any the wiser. It seems that nothing is safe anymore. Researchers have shown that even super yachts, which would appear immune as a result of their isolation, are vulnerable to hacking. Jay Kelley of Menlo Security explains how attackers can exploit everything from connected homes and businesses through to cars, hotels and even boats. The solution to the problem, he argues, is web isolation, handling web activity in virtual, disposable containers to keep malware well away from your critical systems so that you can explore the Internet in safety.